Sam Cromie, Hannah Quinn-Gates, Paul Fagan, Mengistie Rebsso - Cromie, Samuel (My University, 2017)
Tearfund has implemented a programme of establishing and facilitating a network self-help groups (SHG) comprising the poorest people in Ethiopian Society since 2002. The SHGs follow a carefully defined philosophy based initially on the self-help group movement run by MYRADA India and adapted to the Ethiopian Context with the assistance of Tearfund Ireland, Tearfund Netherlands, The Dutch Ministry of Foreign Affairs (BuZa) and Irish Aid. Previous research has examined the cost-benefit of Ethiopian self-help groups and found a very positive cost benefit ratio (Venton, et. al., 2013). However, this research has not documented, other than anecdotally, the social and psychological benefits experienced by the individuals participating in SHGs or the mechanisms involved in bringing about these benefits This research aims to: · Evaluate the impact of SHGs on the psycho-social wellbeing of their members · Elucidate the features of SHGs which promote, and those that may hamper, achieving this impact Ten SHGs from Wolaita (SNNPR) and Adama (Oromiya) were selected for this study – five young (less than two years) and five more mature (more than five years). The SHGs were chosen to include high- (5), low- (1) and average- (4) functioning groups. A survey of individual members, a focus group with the SHG as a whole and interviews with key informants served to gather qualitative and quantitative data about both the individual and the SHG. Quantitative analysis was complemented by a thematic analysis of the open-ended questions in the survey and focus groups. We found that, as well as having a clear impact on the financial circumstances, SHGs are also impacting members’ lives in a variety of ways. Older SHGs assessed the impact of the SHG as being greater and they scored more highly on measures of psychological and social wellbeing, indicating that the impact of the SHG increases over time. Themes that emerged from the members’ discussion of the impact of the SHG were increased finances, moving from poverty to provider, moving from dependence to independence, education gained through the SHG, moving from social isolation to participation, social development, personal development and spiritual development. We identified several key elements of SHGs that seem to be critical in achieving these positive outcomes. The defined rules and bylaws of each SHG provide a strong structure for members to interact with clear expectations and boundaries. For of members who, in their own words, have come from lives with no structure, no role, no one to meet, no process to follow, the “hard” fixed aspects of the SHG are very empowering. These are complemented by a set of values and principles – of equality, sharing, mutual support and forgiveness. The evidence is strong that the SHGs manage to develop an environment in which all members are valued and get to participate, where dominance by one or two individuals is rare and where conflicts are, generally, effectively dealt with within the group. These “soft” aspects of the SHGs are to some extent built into the structure, but there is a strong indication that facilitators are a critical part of promoting this culture by providing strong models of the values and attitudes that are reported as being characteristic of the SHGs – acceptance, love, forgiveness. A strong theme in both the impact and mechanism sections above is education or training. It is clear that this is an aspect of the SHG that participants find very empowering. Given the low education level that most of the participants are coming from, the opportunity to gain knowledge and skills in areas as diverse as financial management and hygiene is very empowering.
PUBLISHED
Evaluates the psycho-social outcomes and mechanisms of self-help groups in Ethiopia thus informing policy on the directing of public funds towards the support of self-help groups.
Keywords: Self-help groups; Ethiopia; Tearfund; Psycho-social wellbeing; Inclusive Society; International Development; EMPOWERMENT; ETHIOPIA; PSYCHOSOCIAL OUTCOME; Poverty & Social Exclusion; Psychological Well-being; SELF-HELP; SELF-HELP GROUP; mixed methods study